Association between physical activity, smartphone usage, and obesity risk among Korean adolescents: A cross-sectional study based on 2021 Korean adolescent health behavior survey - Haoyuan Li; Jaeyoung Choi; Aram Kim; Guifang Liu (Acta Psychologica)
Background: With adolescent obesity rates steadily rising, it has become crucial to identify modifiable risk factors to develop effective interventions. This study explores the associations between physical activity (PA) levels, smartphone usage, and obesity risk among Korean adolescents, aiming to inform the design of targeted health promotion programs to mitigate obesity rates in this demographic. Methods: This cross-sectional analysis used data from 50,407 Korean adolescents who participated in the 2021 Adolescent Health Behavior Online Survey. Descriptive statistics and chi-square tests compared PA patterns, sedentary behavior, and smartphone usage between adolescents with obesity and those without obesity. To examine the impact of key exposure factors-including PA, muscle strengthening exercises (MSE), sedentary behavior, and smartphone usage-on obesity risk, binary logistic regression models were used, adjusting for grade level, economic status, and other potential confounders. Results: Male adolescents exercising “3–4 times/week” had a significantly higher obesity risk compared to those with no PA (OR = 1.144, 95 % CI: 1.032–1.267, p < 0.01). Similarly, females exercising “3–4 times/week” (OR = 1.208, 95 % CI: 1.048–1.393, p < 0.01) or “≥ 5 times/week” (OR = 1.333, 95 % CI: 1.087–1.636, p < 0.01) also showed increased risk. Both males and females participating in high-intensity PA (HIPA) “1–2 times/week” were at higher risk (males: OR = 1.110, 95 % CI: 1.011–1.219, p < 0.01; females: OR = 1.427, 95 % CI: 1.283–1.587, p < 0.001). Conversely, MSE was linked to a significant reduction in obesity risk across most frequency groups, especially in males (OR = 0.450, 95 % CI: 0.399–0.508, p < 0.001). For sedentary behavior, females with ≥6 h of weekday non-learning sedentary time (SWD-N) had increased obesity risk (OR = 1.210, 95 % CI: 1.002–1.462, p < 0.01), as did males with ≥6 h of weekend sedentary time (SWK-N) (OR = 1.334, 95 % CI: 1.154–1.542, p < 0.001) and females with ≥6 h of weekend smartphone usage (SPWK_TM) (OR = 1.567, 95 % CI: 1.066–2.303, p < 0.01). Conclusions: The findings reveal complex relationships between PA, MSE, sedentary behavior, and smartphone usage in the context of adolescent obesity. Certain PA levels, particularly 3–4 times/week and ≥ 5 times/week for females, and HIPA frequency were associated with increased obesity risk. In contrast, MSE significantly reduced obesity risk across genders, with the most substantial effects observed in males engaging in MSE ≥ 5 times/week. Only associations meeting the p < 0.01 threshold were interpreted in this study to ensure robust conclusions. These results emphasize the importance of promoting MSE and balanced sedentary behavior patterns to reduce adolescent obesity risk, suggesting health policies should address these factors with a focus on gender-specific and age-specific strategies. However, limitations such as the lack of nutrition data, unassessed PA intensity, and HIPA duration should be addressed in future research.